Flexural strength, biocompatibility, and antimicrobial activity of a polymethyl methacrylate denture resin enhanced with graphene and silver nanoparticles - Bacali, Cecilia; Baldea, Ioana; Moldovan, Marioara; Carpa, Rahela; Olteanu, Diana Elena; Filip, Gabriela Adriana; Nastase, Vivi; Lascu, Liana; Badea, Mandra; Constantiniuc, Mariana; Badea, Florin (Clinical oral investigations, 2020)
The study evaluates the effect of adding graphene-Ag nanoparticles (G-AgNp) to a PMMA auto-polymerizing resin, with focus on antibacterial activity, cytotoxicity, monomer release, and mechanical properties.
Published online: 16 November 2019
Gesehen am 13.08.2020